DIET-INDUCED ASPECTS OF AN EXPERIMENTAL MODEL OF OBESITY (World Bulletin of Public Health, 2026)
Obesity is currently one of the most widespread pathologies. In Uzbekistan, obesity and conditions associated with it affect 20.4% of the total population; specifically, this figure stands at 22.1% among women and 11.5% among men [3]. Diseases linked to metabolic syndrome—particularly obesity—drive an increase in the incidence of type 2 diabetes and prediabetes. The specific activity of visceral adipose tissue exacerbates insulin resistance, as this tissue is characterized by high lipolytic activity and a diminished response to the antilipolytic action of insulin. Consequently, levels of free fatty acids rise, and high concentrations of these acids enter the liver, inducing hyperglycemia, hyperinsulinemia, and insulin resistance; this, in turn, increases triglyceride synthesis and lowers levels of high-density lipoprotein (HDL) cholesterol [1]. Adipose tissue—especially visceral fat— produces leptin, tumor necrosis factor (TNF), various growth factors, angiotensinogen, and a range of other hormonally active substances. The overproduction of these substances leads to a desensitization of the hypothalamus and the subsequent development of insulin resistance within the context of metabolic syndrome [2]. Debate persists regarding which of these factors plays the primary role in the pathogenesis of metabolic syndrome: insulin resistance, hyperinsulinemia, or obesity.